2018
DOI: 10.3390/ijms19010206
|View full text |Cite
|
Sign up to set email alerts
|

Mustn1: A Developmentally Regulated Pan-Musculoskeletal Cell Marker and Regulatory Gene

Abstract: Abstract:The Mustn1 gene encodes a small nuclear protein (~9.6 kDa) that does not belong to any known family. Its genomic organization consists of three exons interspersed by two introns and it is highly homologous across vertebrate species. Promoter analyses revealed that its expression is regulated by the AP family of transcription factors, especially c-Fos, Fra-2 and JunD. Mustn1 is predominantly expressed in the major tissues of the musculoskeletal system: bone, cartilage, skeletal muscle and tendon. Its e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 61 publications
0
27
0
Order By: Relevance
“…The transformation of intestinal tissues during the change to exogenous feeding shortly after hatching could further influence this peak value (Ostaszewska, 2005), as it also involves the formation of collagenous matrices (Nakase et al, 2006). Together with COL1A, the skeletal marker MUSTN1 (Hadjiargyrou, 2018; Lombardo et al, 2004) showed significant expression maxima during the increasing skeletal growth and ossification at 280 dd.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transformation of intestinal tissues during the change to exogenous feeding shortly after hatching could further influence this peak value (Ostaszewska, 2005), as it also involves the formation of collagenous matrices (Nakase et al, 2006). Together with COL1A, the skeletal marker MUSTN1 (Hadjiargyrou, 2018; Lombardo et al, 2004) showed significant expression maxima during the increasing skeletal growth and ossification at 280 dd.…”
Section: Discussionmentioning
confidence: 99%
“…As this study focuses primarily on early ontogeny, we included genes that influence general development as well as genes that regulate local muscle formation (Degenhardt & Sassoon, 2001; Kimmel et al, 2001). As muscle localization during development is controlled by the musculoskeletal system (Sefton & Kardon, 2019), additional gene markers for collagenous (Gelse et al, 2003) and skeletal development (Gersch & Hadjiargyrou, 2009; Hadjiargyrou, 2018) were included. The goal of this study was to provide a basic expression profile of developmental genes to gain insight into early ontogeny, and in particular, the myogenesis of pikeperch.…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of VSMC-preferentially expressed or -specific transcripts identified in our study were related to muscle differentiation and contractility. Apart from well-known VSMCs transcripts (such as Acta2, Myh11, desmin and Tgln ), our analysis highlighted the expression of markers like NR4a1 (coding for nuclear receptor subfamily 4, group A, member 1, involved in SMC proliferation) (Hinze et al, 2013; Yu et al, 2015), Pdlim3 (coding for actinin-associated LIM protein, involved in myocyte stability (Zheng et al, 2010), Mustn1 (regulating myoblast differentiation) (Hadjiargyrou, 2018; Liu et al, 2010), and Pln (coding for phospholamban, which regulates the sarcoplasmic reticulum Ca 2+ ATPase (SERCA) activity and muscle contractility) (Kranias and Hajjar, 2012). Surprisingly, about half of the genes were strongly upregulated on P15; this indicates that VSMC contractility continued to differentiate between P5 and P15.…”
Section: Discussionmentioning
confidence: 89%
“…GO terms associated with clusters NP3, NP5, oAF2, and oAF3 were related to tissue development, skeletal system morphogenesis, ECM, and anatomical structure formation involved in morphogenesis, respectively, suggesting these populations are important for forming and maintaining the IVD structure. Cells in NP3 expressed MGP and SPP1 , which regulate ectopic tissue calcification, 101 MUSTN1 , a gene expressed in musculoskeletal tissues during development, 102 and CNMD , a protein that promotes chondrocyte differentiation and attenuates osteoarthritis progress by inhibiting catabolic activity 103,104 . COL2A1 and COMP , which encode ECM proteins canonically associated with the NP, 9 were both upregulated in NP5.…”
Section: Discussionmentioning
confidence: 99%